2014
DOI: 10.1111/pbi.12202
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of maize (Zea mays) crop performance: natural variation, incremental improvements and economic impacts

Abstract: Summary Grain yield from maize hybrids continues to improve through advances in breeding and biotechnology. Despite genetic improvements to hybrid maize, grain yield from distinct maize hybrids is expected to vary across growing locations due to numerous environmental factors. In this study, we examine across‐location variation in grain yield among maize hybrids in three case studies. The three case studies examine hybrid improvement through breeding, introduction of an insect protection trait or introduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Both the hybrids produced identical number of kernel rows per ear (Table 2) but planting arrangement affected the number of kernel rows per ear significantly. Planting in wide rows or in twin-rows resulted in identical but significantly lower number of kernel rows per ear compared with narrow rows at 50 cm, which agrees with Abuzar et al [14] who observed progressive decrease in kernel rows per ear with increasing plant density from 60,000 to 140,000 plants per ha suggesting that compared with other traits in modern hybrids the resistance of kernel rows per ear to plant competition might be less [12].…”
Section: Experiments 1 Planting Arrangement Population Density Effectssupporting
confidence: 87%
See 1 more Smart Citation
“…Both the hybrids produced identical number of kernel rows per ear (Table 2) but planting arrangement affected the number of kernel rows per ear significantly. Planting in wide rows or in twin-rows resulted in identical but significantly lower number of kernel rows per ear compared with narrow rows at 50 cm, which agrees with Abuzar et al [14] who observed progressive decrease in kernel rows per ear with increasing plant density from 60,000 to 140,000 plants per ha suggesting that compared with other traits in modern hybrids the resistance of kernel rows per ear to plant competition might be less [12].…”
Section: Experiments 1 Planting Arrangement Population Density Effectssupporting
confidence: 87%
“…Improvement of agronomic management practices also contributed greatly to increasing grain yields [11]. However, the yield performance differs remarkably across hybrids depending on environmental conditions [12] and agronomic management. Among the agronomic factors influencing the grain yield of maize, plant population density is the most important one [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…With increasing knowledge on plant response to drought stress and molecular understanding of gene networks underlying the physiological processes that impact drought tolerance, monogenic drought tolerance in maize has become possible by a transgenic approach. Indeed, there are multiple examples of the validation of the efficacy of transgenes in elite hybrids under field conditions (Castiglioni et al, 2008;Guo et al, 2014;Habben et al, 2014;Leibman et al, 2014;Nuccio et al, 2015;Shi et al, 2015). With the advent of CRISPR-Cas enabled advanced technology, a new technique is now available to provide new sources of genetic variation for plant breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Grain yield stability can be defined as the ability of the hybrid to produce grain despite the environmental factor variations that can occur in different localities and different years (Leibman et al 2014). Apart from the grain yield, yield stability is one of the most significant traits for genetic potential increase through time (Tollenaar and Lee 2002).…”
Section: Discussionmentioning
confidence: 99%